STRATEGI PELAYANAN KESEHATAN MELALUI PROGRAM PUSKESMAS KELILING DALAM MENINGKATKAN KESADARAN HIDUP SEHAT PADA MASYARAKAT - Lulu Andriani Sulasti; Siti Khotimah; Hj. Siti Fatonah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Limited access to health facilities in remote areas is a major challenge in Indonesia. Mobile Community Health Centers (Puskesmas Keliling) offer an innovative solution to reach underserved communities. This literature-based study examines their role in increasing public awareness of healthy living. Findings show that these mobile centers effectively expand access to basic health services, improve knowledge of clean and healthy behaviors (PHBS), and strengthen preventive programs. Key challenges include limited human resources, infrastructure, and funding. Recommended strategies are enhancing public education, cross-sector collaboration, capacity building for health workers, and digital technology use. These approaches make Mobile Community Health Centers effective in promoting healthy living and equitable health service distribution.